Science at the White House A Political Liability - Burger, Jr (Johns Hopkins University Press, 2019)
Originally published in 1980. In 1973 the US president's Office of Science and Technology was eliminated, a victim of its own incongruity. It was not, as was popularly proclaimed at the time, simply because the Nixon administration was particularly hostile to the scientific and academic communities. It was eliminated, argues physician-scientist Edward J. Burger Jr., because the office had tried to do its job too well-and had become a political liability. Science at the White House takes a critical look at the role of science advisers to the president and recounts the many conflicts that occurred as science and politics converged. Burger draws on his own six years of experience in the White House Office of Science and Technology in the 1970s. His book is filled with firsthand descriptions of the government's handling of such issues as national health care, environmental regulation, population control, and biomedical research.